THE IMPACT OF INFRASTRUCTURE ON STRATEGIC SECTORS EXPENSES FOR POVERTY: THE CASE IN ASEAN 4 - Ati Musaiyaroh; Suryaning Bawono (UNEJ e-Proceeding)
The development of state infrastructure encourages economic growth. This is supported by the availability of adequate resources both in terms of quality of human resources, nature, and technology. This phenomenon is a reflection of the state government in development activities. Infrastructure development is a driver of growth by reducing poverty and reducing unemployment. The objectives of the study were to analyze Appropriate strategies in economic development especially on poverty issues in ASEAN 4 (Indonesia, Malaysia, The Philippines, and Thailand). The variables that Become the object of research are poverty, infrastructure (education and health), GDP per capita, the Gini index, government expenditure and the unemployment rate. The research method used is the Panel Generalized Method of Moment (PGMM). The results of PGMM estimates provide evidence that infrastructure in the form of health care, per capita GDP and government expenditure has significant implications for poverty in ASEAN 4. The results illustrate that the government for each country needs to a make improvement and additional Infrastructure as an investment in economic growth. This can be done by Mobilizing monetary and fiscal policies, especially Reviews those that lead to an emphasis on poverty.